After the Strike is Before the Strike. On the Current Development of Collective Bargaining Relationships at Deutsche Bahn - Berndt Karl Keller (Wirtschaftsdienst)
Abstract At the beginning of the 2000s, some professional unions were formed that replaced the old system of collective bargaining unity. In 2010, the Federal Labour Court finally permitted the collective bargaining plurality in principle. With the Collective Bargaining Unity Act of 2015, the power of smaller professional unions was supposed to be narrowed down again. The rules in the Collective Bargaining Unity Act, however, are too vague to prevent union conflicts from occurring within a company. The Deutsche Bahn offers a good example.